Directional dependency of mechanical properties in gallium phosphide semiconducting material - Bioud, nadhira (International Journal of Physical Research, 2024)
The aims of this contibution is to investigate the directional dependency of mechanical properties of gallium phosphide (GaP) semiconduct-ing material using the experimental stiffness elastic constants Cij reported in the litterature. These characteristics are visible by analysis and visualization of elastic tensors. The spatial dependencies of the Young’s modulus, linear compressibility, shear modulus, and Poisson’s ratio in GaP binary compound were calculated and schematized in graphical representations. Data analysis shows that the maximum value Emax of Young's modulus was estimated at around 166.7 GPa, while its minimum value Emin was estimated at around 102.5 GPa, which gives a ratio of approximately Emax/Emin ≈ 1.63, while for the Poisson’s ratio υ, the maximum value υmax of υ was estimated at around 0.43, while its minimum value υmin was estimated at 0.025, which gives a rate of approximately υmax/υmin ≈ 17.5. The Debye temperature was also calculated, it is estimated at about 482.4 K, it is in good agreement with the experimental one (493 K) reported in the litterature, and the deviation between these two values is less than 2.2%.